A comparative analysis of young tennis player target accuracy when using balls inflated under different pressures - Крылов, Дмитрий (Slobozhanskyi Herald of Science and Sport, 2017)
Dmytro Krylov Purpose: make a comparative analysis of the target accuracy of ten-year tennis players in performing test exercises with balls with a pressure of 75% of the standard and balls with standard pressure. Material & Methods: in the study participated 8 tennis players of ten years of age, the group 5 years of training. In the course of the research, the following methods were used: analysis and generalization of literature sources, analysis of documentary materials, testing, method of expert evaluations. Results: replacing balls with a pressure of 75% of the standard for standard leads to a deterioration in the target accuracy of ten-year tennis players, which is a consequence of distortion of the technical characteristics of movements. Conclusion: results of the study indicate the need for correction of the technique of players of this age in the transition from balls with a pressure of 75% from the standard to standard.